PLURALISME ADALAH FUNDAMENTALISME - Baco Sarluf (DIALEKTIKA, 2019)
ABSTRACT Fundamentalism can be understood as a movement in a stream, ideology or religion that seeks to return its people to what is believed to be the foundations or principles (fundamental). The effort is done because according to them the beliefs of the people and the practice of religious teachings have deviated from the basic or principal religion. In an attempt to realize their understanding, fundamentalists often clash with other religions or with groups that disagree with them. One of the offers of improvement comes from a group of supporters of pluralism, namely the need for recognition of the truth of other religions. That means, all religions within him contain the truth of God in a relative portion. Their motto "All truth (religion) is relative". This motto affirms all truths as forms of relativity but at the same time affirms relativity as the only truth. Besides, by saying that all truths are relative, they have created counter-groups to deal with the faithful followers of formal religions that still remain fundamentalist. Keywords: Fundamentalism, Pluralism, Relativeism